2019
DOI: 10.1155/2019/1720270
|View full text |Cite
|
Sign up to set email alerts
|

Automated Estimation of Acute Infarct Volume from Noncontrast Head CT Using Image Intensity Inhomogeneity Correction

Abstract: Identification of early ischemic changes (EIC) on noncontrast head CT scans performed within the first few hours of stroke onset may have important implications for subsequent treatment, though early stroke is poorly delimited on these studies. Lack of sharp lesion boundary delineation in early infarcts precludes manual volume measures, as well as measures using edge-detection or region-filling algorithms. We wished to test a hypothesis that image intensity inhomogeneity correction may provide a sensitive meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Thus, combining information from both imaging modalities best estimates the extent of ischemic injury and prognosis. Automated software to measure CT hypodensity is evolving, but, regardless, clinicians are able to recognize individuals in whom there are substantial noncontrast CT changes outside of the current CT perfusion core and account for these changes when assessing treatment decisions and prognosis. Imaging discordance between the 2 modalities was frequent and did not alter EVT treatment effect.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, combining information from both imaging modalities best estimates the extent of ischemic injury and prognosis. Automated software to measure CT hypodensity is evolving, but, regardless, clinicians are able to recognize individuals in whom there are substantial noncontrast CT changes outside of the current CT perfusion core and account for these changes when assessing treatment decisions and prognosis. Imaging discordance between the 2 modalities was frequent and did not alter EVT treatment effect.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of segmentation, a lack of a sharp boundary delineation hinders and delays the identification process. Cauley et al, tested a hypothesis and proved that image intensity inhomogeneity provides a sign for identifying the subtle hypo-density regionals which, in turn, is characteristic of ischemic infarct [56]. Ledig C et al, proposed a probabilistic framework for automatic segmentation of MRI using "multi-atlas label propagation" [57].…”
Section: Mri Based Methodsmentioning
confidence: 99%
“…On the other hand, CT findings associated with early ischemic changes are weak and difficult to detect on tomograms. For example, Akasaka et al reported that when MRI was used as the primary standard for ischemic stroke diagnosis, the average sensitivity for stroke diagnosis from noncontrast head computed tomography (NCCT) data was 26.5% among 14 radiologists [18]. Thus, an automated system assisting medical experts in the diagnosis of acute ischemic stroke on tomograms can be useful in clinical settings.…”
Section: Literature Reviewmentioning
confidence: 99%